Analisis Strategi Pemasaran Kartu Perdana Dan Voucher Telkomsel Di Jakarta Barat: Analysis of Telkomsel Prepaid Card and Voucher Marketing Strategies in West Jakarta - Anastasia Kurniasi Lomu Kotan; Furi Indriyani (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
The rapid development of the telecommunications industry requires every Telkomsel outlet to implement effective business management strategies to remain competitive. Telkomsel Authorized Partner Kembangan, West Jakarta, faces challenges such as price competition, promotional rivalry, and changes in consumer behavior, necessitating a systematic analysis to determine appropriate strategies. This study aims to analyze the internal and external factors of the company and formulate business development strategies using the SWOT approach. The research method is qualitative descriptive, with data collected through observation, interviews, and documentation studies. Analysis was conducted using IFAS and EFAS matrices to identify the company’s Strengths, weakness, opportunities, and threats. The results show that the company’s internal Strengths outweigh its weakness, while external opportunities are greater than threats. Telkomsel Authorized Partner Kembangan is positioned in the Growth and Build quadrant, indicating that aggressive growth strategies are recommended, such as leveraging brand image, wide network coverage, strategic distribution locations, and complete product offerings to increase sales. The study also highlights the importance of improving human resource competencies, optimizing digital promotions, educating partner outlets, and developing digital services to maintain competitive advantage.